2018
DOI: 10.2196/jmir.7898
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Reality in Patients with Eating Disorders: Systematic Review

Abstract: BackgroundPatients with eating disorders are characterized by pathological eating habits and a tendency to overestimate their weight and body shape. Virtual reality shows promise for the evaluation and management of patients with eating disorders. This technology, when accepted by this population, allows immersion in virtual environments, assessment, and therapeutic approaches, by exposing users to high-calorie foods or changes in body shape.ObjectiveTo better understand the value of virtual reality, we conduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 54 publications
(66 reference statements)
1
89
0
2
Order By: Relevance
“…VR makes it possible to present the patients' bodies and to help them build awareness of the distortion of their body image and, subsequently, to confront and correct the distortions, which results in a more realistic body image and decreasing the dissatisfaction with body image (Wiederhold, Riva, & Gutiérrez-Maldonado, 2016). On the basis of research it can be stated that virtual reality is an acceptable and promising tool in therapy of eating disorders (Clus, Larsen, Lemey, & Berrouiguet, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…VR makes it possible to present the patients' bodies and to help them build awareness of the distortion of their body image and, subsequently, to confront and correct the distortions, which results in a more realistic body image and decreasing the dissatisfaction with body image (Wiederhold, Riva, & Gutiérrez-Maldonado, 2016). On the basis of research it can be stated that virtual reality is an acceptable and promising tool in therapy of eating disorders (Clus, Larsen, Lemey, & Berrouiguet, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These studies used a head-mounted display (HMD) through which participants can be immersed in an interactive virtual reality scenario [19]. Through the HMD, the experimenter may provide different sensory input, as well as synchronize participants' movements with the generated virtual feedback (e.g., avatar movements, or reaching virtual objects) [20]. In order to increase the sense of immersion, feedback across different sensory channels is provided, such as, visual, acoustic, and tactile.…”
Section: Discussionmentioning
confidence: 99%
“…The growing development of new technologies and the interest in applying them in the field of psychology have led to the development of novel virtual reality (VR) systems for neuro-rehabilitation [18], or the treatment of different mental health disorders [19][20][21][22] with the aim of generating an engaging and realistic virtual world in line with the needs of the person [23]. Applying virtual reality in psychology has one major advantage.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of eating disorders, VR uses visual stimuli to control craving for high-calorie foods, and to change the patient's body image [51]. A meta-analysis on the treatment of bulimia nervosa and binge eating disorder showed that VR therapy resulted in changes in the individual's body image, increased motivation to change, increased self-esteem, and reduced body image disturbances, binge eating, and purging behavior [52].…”
Section: Addiction and Eating Disordersmentioning
confidence: 99%